2015
DOI: 10.1007/978-3-319-20579-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking: The Future of Cell Preservation Strategies

Abstract: With established techniques cryopreservation is often viewed as an "old school" discipline yet modern cryopreservation is undergoing another scientific and technology development growth phase. In this regard, today's cryopreservation processes and cryopreserved products are found at the forefront of research in the areas of discovery science, stem cell research, diagnostic development and personalized medicine. As the utilization of cryopreserved cells continues to increase, the demands placed on the biobankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…A possible explanation for this finding is that the cryopreservation protocol, which produces some degree of cell loss, may act as a selection method. In this way, HuSCs expressing higher levels of anti‐apoptotic factors or molecules that make them more resistant to oxidative stress or preserve membrane stability (Baust, Corwin, VanBuskirk, & Baust, ; Bissoyi, Nayak, Pramanik, & Sarangi, ) would thus be selected during the cryopreservation and recovery process. In studies with myocardial cells, prior cryopreservation has been shown to increase the proliferation capacity of the cells as well as reduce their immunogenicity (Yokomuro et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this finding is that the cryopreservation protocol, which produces some degree of cell loss, may act as a selection method. In this way, HuSCs expressing higher levels of anti‐apoptotic factors or molecules that make them more resistant to oxidative stress or preserve membrane stability (Baust, Corwin, VanBuskirk, & Baust, ; Bissoyi, Nayak, Pramanik, & Sarangi, ) would thus be selected during the cryopreservation and recovery process. In studies with myocardial cells, prior cryopreservation has been shown to increase the proliferation capacity of the cells as well as reduce their immunogenicity (Yokomuro et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One point of discussion has been the use of regulatory-compliant protein sources (such as foetal bovine serum or human serum) [83] or xeno-protein free solutions [84] as a CPA carrier media. Some commercially available GMP-compliant CPA solutions have recently become available (CryoStor™, BioLife) [2]. For specific types of non-autologous cell therapies, the importance of recording and testing of cell provenance throughout the development of master and working cell banks is an additional important consideration [85].…”
Section: Considerations For Gmp Transfer Of Cell Therapy Cryopreservamentioning
confidence: 99%
“…These considerations sometimes introduce new challenges that may not have been important in the original laboratory studies on that particular cell therapy. One such consideration is product storage (cryobanking), which is often required to sustain cell therapy delivery to the end user facilities at the required time, providing a quality assured product with required safety and potency characteristics [1,2]. Cryopreservation in its various forms is one of the main facilitatory technologies for cell therapies to be able to meet these demands.…”
mentioning
confidence: 99%
“…However, this method will only permit storage for a few days and rules out the possibility of being a desirable method for long-term storage or delivey. Thus, the preservation at deep cryogenic temperatures (ranging from -196°C to approximately -150°C) where cells, tissues, cell-based products or organs are suspended in a tissue medium with one or more cryoprotectants (CPAs), a process named cryopreservation, is the only technology that enables "holding the biological clock" of cell-based products and facilitates the "on demand" access of patients to the treatments in a clinic far from the manufacturer [1,2] Theoretically, if cryopreservation works successfully, it should provide a quality product that ensures the previous characteristics are kept. However, during the cryopreservation process several mechanisms lead to cell damage and compromise product quality and integrity.…”
Section: Introductionmentioning
confidence: 99%